Enxágue bucal com carboidrato não melhora o desempenho em sprints repetidos - Bortolotti, H.; Santos Oliveira, R.; Serpeloni Cyrino, E.; Altimari, L. R. (Revista Brasileira de Cineantropometria e Desempenho Humano, 2013)
The objective of this study was to evaluate the effect of a carbohydrate mouth rinse on the repeated sprint ability (RSA) of young soccer players. Nine youth soccer players (15.0 ± 1.5 years; 60.7 ± 4.84 kg; 1.72 ± 0.05 m; 20.5 ± 1.25 kg/m2) were selected. The athletes were submitted to an RSA test consisting of six sprints of 40 m (going/return = 20 m + 20 m), separated by 20 s of passive recovery, under three experimental conditions: carbohydrate mouth rinse (CHO) or placebo (PLA) and control (CON). The mouth rinses containing CHO or PLA were administered 5 min and immediately before the beginning of the test in doses of 100 mL. The best sprint time (RSAbest), mean sprint time (RSAmean), and drop-off in sprint performance (fatigue index) were determined for the different treatments. One-not identify significant differences (p> 0.05) in RSAbest (CHO way ANOVA for repeated measures did = 7.30 ± 0.31 s; PLA = 7.30 ± 0.30 s; CON = 7.26 ±0.16 s), RSA mean (CHO = 7.71 ± 0.30 s; PLA = 7.71 ± 0.25 s; CON = 7.66 ± 0.24s), or fatigue index (CHO = 5.58 ± 2.16%; PLA = 5.77 ± 3.04%; CON = 5.55 ±3.72%). The results suggest that a carbohydrate mouth rinse does not improve the repeated sprint performance of young soccer players.